ANALISIS KEBANGKRUTAN PERUSAHAAN MELALUI PERBANDINGAN MODEL ALTMAN Z-SCORE, MODEL SPRINGATE’S, DAN MODEL FULMER PADA INDUSTRI SEMEN DI INDONESIA - Peter Peter; Herlina Herlina; Jessica Wiraatmaja (Ultima Management : Jurnal Ilmu Manajemen, 2021)
Abstract- The aims of this research is to determine the difference between the rate of bankrupcy Altman Z- Score Model, Springate’s Model, and Fulmer Model, as well as measures which model is most accurate in predicting bankruptcy at cement companies that listed at Indonesia Stock Exchange period 2014 – 2018 (PT. Indocement Tunggal Prakasa Tbk, PT. Semen Baturaja Tbk, PT. Holcim Indonesia Tbk, and PT. Semen Indonesia Tbk). The Collection of the data that we used is documentation, that we collecting data of financial reports from 2014- 2018 periods. In this research, ratio analysis and regression were used for data analysis. Result of this research showed that there were differences of bankrupcy prediction based on the Altman Z- Score Model, Springate’s Model, and Fulmer Model. The highest level of accuracy is the model of Fulmer. Keywords: Altman Z- Score Model; Bankruptcy; Fulmer Model; Springate’s Model